On the Realistic Radio and Network Planning of IoT Sensor Networks - Kanaris, Loizos; Sergiou, Charalampos; Kokkinis, Akis; Pafitis, Aris; Antoniou, Nikos; Stavrou, Stavros (My University, 2019)
Planning and deploying a functional large scale Wireless Sensor Network (WSN) or a Network of Internet of Things (IoTs) is a challenging task, especially in complex urban environments. A main network design bottleneck is the existence and/or correct usage of appropriate cross layer simulators that can generate realistic results for the scenario of interest. Existing network simulators tend to overlook the complexity of the physical radio propagation layer and consequently do not realistically simulate the main radio propagation conditions that take place in urban or suburban environments, thus passing inaccurate results between Open Systems Interconnection (OSI) layers. This work demonstrates through simulations and measurements that, by correctly passing physical information to higher layers, the overall simulation process produces more accurate results at the network layer. It is demonstrated that the resulting simulation methodology can be utilized to accomplish realistic wireless planning and performance analysis of the deployed nodes, with results that are very close to those of real test-beds, or actual WSN deployments.
Keywords: WSN; IoT; Radio planning; Physical layer; Network layer; Simulation; Sensor; Cooja; TruNET wireless